The innovative model of supporting short food supply chains by a local government unit on the example of the municipality of Kamienna Góra - Raftowicz, Magdalena; Solarz, Krzysztof (Innowacyjny model wspierania krótkich łańcuchów dostaw żywności przez jednostkę samorządu terytorialnego na przykładzie Gminy Kamienna Góra, 2024)
Aim: The main goal of this article is to present the innovative model for supporting short food supply chains and to assess the effectiveness of actions taken by local authorities to develop the local market, using the municipality of Kamienna Góra as a case study. Methodology: The article is based on a critical analysis of relevant literature and original research, including in-depth interviews with the Deputy Mayor and the Director of the Business Incubator of the Municipality of Kamienna Góra, the analysis of the municipality’s strategic documents, and personal observations. Results: The research findings indicate that the implementation of the innovative model for supporting short food supply chains has contributed to the development of the local agricultural market. However, the continued success of this system requires ongoing support from the local government. Implications and recommendations: The research conclusions may contribute to the development of recommendations for public policies that support the growth of local food markets in a more coherent and sustainable manner at the national level. Originality/value: The exploration of this topic is justified by the increasing need to support local food markets as a tool for the sustainable development of rural areas.
Biblioteka Regionalisty = Regional Journal, 2024, Nr 24, s. 116-126
Keywords: short food supply chains; local government; innovative model; Kamienna Góra; krótkie łańcuchy dostaw żywności; samorząd terytorialny; innowacyjny model